ESTIMATION OF BIOLOGICAL PARAMETERS OF SQUID (LOLIGO SPP) CAUGHT IN THE WATERS OF TUBAN REGENCY - Setyohadi, Daduk; Kartikasari, Wahida; Setyanto, Arief; Wiadnya, Dewa Gede Raka; Harlyan, Ledhyane Eka; Sunardi, Sunardi; Nabilla, Azma Salma (Journal of Environmental Engineering and Sustainable Technology, 2024)
Squid (Loligo spp.) belongs to the Cephalopoda group (squid, cuttlefish, octopus) and is one of the primary export commodities in the fisheries sector. National squid production increased by 5.5%, from 193,583.82 tons in 2020 to 204,156.28 tons in 2021. However, the potential sustainable catch in the Java Sea (WPPNRI 712, including the Madura Strait) has experienced an average annual decline of 1.9% from 2017 to 2022, dropping to 66,608 tons in 2022. This study aims to identify the species composition of squid, analyze length-weight relationships, and determine the mantle length at first gonad maturity (Lm). Data were obtained from fixed lift-net catches and analyzed in the Fisheries Exploitation Laboratory of Universitas Brawijaya. The results identified two main species: Photololigo duvaucelli (Indian squid) and Sepioteuthis lessoniana (bigfin reef squid). The composition of squid catches was 1.29% in purse seine operations and 2.91% in payang (seine net) operations. The length-weight relationship of both species exhibited a negative allometric growth pattern, where length growth outpaces weight gain. The sex ratio between males and females was balanced for both species. The mantle length at first gonad maturity (Lm) was greater than the mantle length at first capture (Lc), indicating that the catch was dominated by immature squid. These findings highlight the need for minimum catch size regulations to ensure the sustainability of squid resources in the Tuban waters.